Distribution of Chlorophyll Concentrations Using Two Channel Terra MODIS Satellite Images in The Ketingan Coastal Area, Sidoarjo - Siti Zainab; Minarni Nur Trilita; Bagas Aryaseta (Nusantara Science and Technology Proceedings, 2023)
The coast of Ketingan Sidoarjo is a fairly dynamic area, where the lives of fishermen depend on fishing. Ecosystem changes that occur in the coastal area of Ketingan Sidoarjo greatly affect the fishing effort, where one of the parameters that can be observed is the distribution of chlorophyll content from the water bodies on the coast. The purpose of this research is to analyze and map the distribution of chlorophyll content in the coastal area of Ketingan, Sidoarjo. This is based on the fact that researchers have not done much research on chlorophyll using 2-channel Terra Modis satellite imagery, where the best response is on Channel 3 = Rrs_678/Rrs_555, the best model obtained is the 2nd order Polynomial Algorithm Model y = 1.2446 x2 – 1.725 x + 1.0987 with a degree of determination R2= 0.3826.